2008
DOI: 10.1002/cbdv.200890044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Analogues of Flazin, in Particular, Flazinamide, as Promising Anti‐HIV Agents

Abstract: Flazin isolated from the fruiting bodies of Suillus granulatus was found to possess weak anti-HIV activity (EC(50)=2.36 microM, TI=12.1). To establish a SAR study, 46 flazin analogues were synthesized, and their anti-HIV activities were evaluated in vitro. Among them, flazinamide (9a) showed the most potent activity with an EC(50) value of 0.38 microM and a TI value of 312.0. The results suggested that appropriate substituents at positions 3, 1', and 5' of flazin might play a crucial role in determining their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…Both naturally occurring and chemically synthesized β-carbolines exhibited good activities against a set of virus, such as human immunodeficiency virus (HIV) [26,48], herpes simplex virus (HSV) [27,49], vaccinia virus [50], vesicular stomatitis virus [50,51], poliovirus [49], and influenza A and B virus [51]. It was reported that the derivatives with the oxathiazepine 7-membered ring showed potential activities against influenza A and B [51].…”
Section: Resultsmentioning
confidence: 99%
“…Both naturally occurring and chemically synthesized β-carbolines exhibited good activities against a set of virus, such as human immunodeficiency virus (HIV) [26,48], herpes simplex virus (HSV) [27,49], vaccinia virus [50], vesicular stomatitis virus [50,51], poliovirus [49], and influenza A and B virus [51]. It was reported that the derivatives with the oxathiazepine 7-membered ring showed potential activities against influenza A and B [51].…”
Section: Resultsmentioning
confidence: 99%
“…Purity of over 95% was confirmed by elemental analysis with a Perkin Elmer 2400 Series II CHNS/O organic elemental analyzer (Perkin Elmer Inc., Waltham, MA, USA). The compound 7 was prepared according previously published procedures (Tang, et al 2008) to yield off white solid, 23 mg (97%). 1 H NMR ((CD 3 ) 2 SO):  ppm 11.15 (s, 1 H), 8.28-8.08…”
Section: Synthesis Of Amino Acid Derivativesmentioning
confidence: 99%
“…Flazin, a b-carboline alkaloid isolated of Suillus granulatus was found to possess anti-HIV activity [7]. A structure-activity study on 46 flazin synthesized analogues showed a potent anti-HIV activity for flazinamide, which was considered a promising anti-HIV agent [8]. Synthetic b-carboline derivatives bearing a guanidinium groupterminated side chain at C-3 exhibited anti-HIV activity in MT4 cells, inhibiting HIV replication by interfering with TAT-TAR interaction [9].…”
Section: Introductionmentioning
confidence: 99%